Developing the Mali Climate Suitability for Crop Maproom - Dinku, Tufa; Faniriantsoa, Rija; Dinh, Dannie (Accelerating Impacts of CGIAR Climate Research for Africa, 2025)
This report presents the development and key functionalities of the Mali Climate Suitability for Crop Maproom, a collaborative effort between the International Research Institute for Climate and Society (IRI) and Mali’s National Meteorological Agency (Mali-Météo). Utilizing the ENACTS approach to enhance climate data quality by integrating observed and satellite data, the Maproom offers localized climate analyses focused on rainfall and temperature to assess crop suitability. Designed as a decision-support tool, it enables farmers, planners, and policymakers to optimize crop selection and planting schedules, thereby improving agricultural resilience and food security under variable and changing climatic conditions in Mali.